Pengaruh Kegiatan Ekstrakurikuler Terhadap Motivasi Belajar Siswa di SDN 05 Surau Gadang Padang - Damayanti, Yrmina; Oktavi, Theresia Avila Clarita; Mulyatno, Carolus Borromeus (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
Choosing the right extracurricular activities affects the devel-opment of students' social, emotional, and cognitive skills. This study aims to identify the types of extracurricular activi-ties that are of interest to students and analyze their impact on their learning motivation at the Elementary School level. This study was conducted at SDN 05 Surau Gadang Padang with a qualitative approach. Data collection techniques were carried out through in-depth interviews. Interviews were conducted with teachers and students in order to obtain detailed infor-mation. Researchers were directly involved in the data collec-tion process by interacting with teachers and students in the field. The theoretical framework used in this study is Abraham Maslow's learning motivation theory, which emphasizes the importance of intrinsic and extrinsic factors. Extracurricular activities are one of the extrinsic factors that can increase stu-dents' learning motivation. The results showed that students tended to like tahfidz extracurricular activities that were car-ried out routinely every week, especially on Saturdays. Stu-dents' involvement in this favorite extracurricular activity has a positive impact on increasing their learning motivation. The data shows that learning motivation can be seen from stu-dents' enthusiasm in participating in the learning process. Students are encouraged to involve themselves in learning activities by memorizing lesson materials in class. The enthu-siasm of students in learning together shows the emotional and social involvement of students which influences the im-provement of social and emotional skills. The habit of memo-rizing formed through tahfidz activities has a good influence on improving students' basic cognitive abilities.AbstrakMemilih kegiatan ekstrakurikuler  secara tepat berpengaruh terhadap pengembangan keterampilan sosial, emosional, dan  kognitif siswa. Penelitian ini bertujuan untuk mengidentifikasi jenis kegiatan ekstrakurikuler yang diminati oleh siswa serta menganalisis dampaknya terhadap motivasi belajar mereka di tingkat Sekolah Dasar. Penelitian ini dilaksanakan di SDN 05 Surau Gadang Padang dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui wawancara mendalam. Wawancara dilakukan dengan guru dan siswa dengan tujuan dapat memperoleh informasi detail. Peneliti secara langsung terlibat dalam proses pengumpulan data dengan berinteraksi bersama guru dan siswa di lapangan. Kerangka teoretis yang digunakan dalam penelitian ini adalah teori motivasi belajar dari Abraham Maslow, yang menekankan pentingnya faktor intrinsik dan ekstrinsik. Kegiatan ekstrakurikuler merupakan salah satu faktor ekstrinsik yang mampu meningkatkan motivasi belajar siswa. Hasil penelitian menunjukkan bahwa siswa cenderung menyukai kegiatan ekstrakurikuler tahfidz yang dilakukan secara rutin setiap minggu khususnya di hari Sabtu. Keterlibatan siswa dalam kegiatan ekstrakurikuler favorit ini berdampak positif terhadap peningkatan motivasi belajar mereka. Data menunjukkan bahwa motivasi belajar terlihat dari antusiasme siswa  dalam mengikuti proses pembelajaran. Siswa terdorong untuk melibatkan diri  dalam kegiatan belajar dengan  menghafal materi pelajaran di kelas. Antusiasme siswa dalam belajar bersama menunjukkan keterlibatan emosional dan sosial siswa yang berpengaruh pada peningkatan keterampilan sosial dan emosional.   Kebiasaan menghafal yang terbentuk melalui kegiatan tahfidz membawa pengaruh baik pada peningkatan kognitif dasar siswa.